Analisis Efektivitas UKS terhadap Perilaku Hidup Bersih dan Sehat (PHBS) Murid di SD Lambaro Angan Kecamatan Darussalam Kabupaten Aceh Besar - Juhri Abadi; Iskandar Iskandar; Ryan Mulfianda (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2026)
The implementation of Clean and Healthy Living Behavior (PHBS) begins at an early age, particularly among school children, who learn extensively from their surrounding environment through the School Health Program (UKS). Although the family is the primary unit in shaping PHBS habits, parents’ busy schedules often lead children to interact more with teachers and peers at school. This study aims to determine the effectiveness of the UKS program on students’ PHBS at SD Lambaro Angan, Darussalam District, Aceh Besar Regency in 2024. This research employed a cross-sectional design with a population of 321 students and a sample of 76 respondents. Data collection was conducted on March 4, 2024. The results indicate that the UKS program has a significant effect on students’ PHBS, including habits such as washing hands with running water and soap, purchasing healthy snacks at the school canteen, disposing of waste properly, participating in physical exercise, not smoking at school, eliminating mosquito larvae, and using school sanitation facilities (p < 0.05). However, no significant effect was found on activities such as weighing body weight and measuring height. In conclusion, the UKS program is effective in improving students’ PHBS. These findings are expected to provide input for schools to optimize the implementation of UKS and enhance PHBS promotion so that students can apply clean and healthy living behaviors in their daily lives.